Atividades pedagógicas para alunos com dificuldades ortográficas da língua portuguesa nos anos finais do ensino fundamental - Carvalho, Olívia Aparecida (2020)
One of the major problems in the final years of Elementary School is the number of students who do not master basic elements of the standard Portuguese language standard, such as spelling. It is common to notice students who, in the classroom, feel ashamed due to this difficulty, which often also affects their self-esteem when they are targets of bullying for having committed orthographic deviations in posts on their social networks, for example. The school, in turn, remains with activities in which only repetitive copying of misspelled words predominates. As a result of this reality, the theme that generated this dissertation emerged, which, in addition of addressing the concept of banking education, proposed by Freire (2013b) and highlighting the role of every teacher in the integral education of students, it also brings a brief history of literacy in Brazil, considerations and data on illiteracy and functional illiteracy in Brazil, assumptions about the pros and cons of continued progression, and considerations about the importance of the teacher in the process of continued progression. This initial theoretical research was essential to later base the elaboration of pedagogical activities for students with Portuguese language spelling difficulties that can be applied in the final years of Elementary School. It should be noted that the work proposed here is based on the guidelines of the Base Nacional Comum Curricular (BRASIL, 2017).